Pemberian Edukasi pada Kader Posyandu tentang Pengolahan Kacang Hijau dan Kurma sebagai Pemenuhan Kebutuhan Zat Besi Ibu Hamil di Desa Sumberejo Kecamatan Banyuputih Kabupaten Situbondo: Providing Education to Posyandu Cadres about the Processing of Green Beans and Dates to Fulfill the Iron Needs of Pregnant Women in Sumberejo Village, Banyuputih District, Situbondo District - Rahimah, Hayatul; Pratiwi, Ganis Yunita (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Anemia is very susceptible to occurring in pregnant women. The government has made efforts to overcome this problem, but there are still many obstacles experienced, one of which is the non-compliance of pregnant women in consuming blood supplement tablets due to the side effects they experience. Health education or counseling regarding food sources that can meet iron needs needs to be carried out. Apart from that, cooperation from all levels of society is needed, especially posyandu cadres who are part of society closest to pregnant women. Cadres play a bridging role between health workers and pregnant women in providing information. This activity aims to increase cadres' knowledge about the benefits and methods of managing green beans and dates. This activity was carried out by providing education or counseling to female cadres in Sumberejo village, Banyuputih district. This activity was attended by 42 people or 64.6% of the total number of cadres in Sumberejo village. It is known that there has been an increase in knowledge about the importance of iron and dates after the outreach was carried out. Providing education through socialization or counseling is an effective way to disseminate information as an update to knowledge and insight. Providing education needs to be carried out by all components of society, of course, those who interact directly with pregnant women, with the hope of providing information to pregnant women.